ANALISIS KRISIS LEGITIMASI DAN STRATEGI KEBERLANJUTAN PT XYZ AKIBAT KONFLIK LAHAN DENGAN MASYARAKAT - Emalia, Deasy; Shauki, Elvia R. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to analyze the crisis of legitimacy and sustainable development of PT XYZ due to land conflicts with the community, by using legitimacy theory as a basis in helping to analyze by giving meaning to the data findings from research results on the influence of land conflicts on the company's legitimacy and sustainable development. This study uses a case study research strategy and a qualitative research approach, using a single unit analysis, namely PT XYZ. The research method used in this study uses a qualitative descriptive method to help describe and explain the findings of the research data through observation, documentation, and interviews which will then be analyzed using content analysis, thematic analysis, and constant comparative analysis. This study reveals the influence of land conflicts on the legitimacy and sustainable development of companies. This study succeeded in revealing legitimacy repairing as a form of corporate legitimacy crisis, and found that the strategy adopted by companies based on legitimacy theory is a general strategy of "avoid overreaction/don't panic" and a pragmatic legitimacy strategy of "deny", "create monitors". This research is different from previous research because this research was conducted to look at it from an internal company perspective by using primary and secondary data to overcome the limitations of previous research that came from online disclosure media such as company websites and online news as well as conducting observations, documentation and direct interviews with companies.